Proporsionalitas dalam Hisab: Pembacaan terhadap Fatwa Yusuf al-Qaradhawi - Hanif A'la Ilhami; Zul Efendi (Astroislamica: Journal of Islamic Astronomy, 2025)
This study aims to explain the form of al-Qaradhawi's support for the use of astronomical calculations, revealing aspects of proportionality in it, and expressing his comments on the views of other scholars who also support calculations. This research is a qualitative research with a literature approach. Al-Qaradhawi supports calculations to be elevated to the status of a method that has legal power and validity. However, his support for calculation is not absolute, but proportional. The proportional aspect that he puts forward is illustrated by his suggestion to use calculation as a tool to deny moon sighting, namely if calculation finds that the moon is completely unobservable, then all moon sighting testimony must be rejected, even sighting does not need to be carried out from the beginning. Limited to this condition, the government can just base its decision on the results of calculation alone. In contrast, under normal conditions, moon sighting must still be carried out, and remains the main method in (itsbat) determining the beginning of the month. Both of these methods –calculation and sighting- have their portion of use according to their respective conditions. Both still have the power as a wasilah, and become a tool for the government to eliminate differences in welcoming the new month in the same country. Differences in the same country, according to al-Qaradhawi is a difference that ghairu maqbul, can not be tolerated. As for the views of Ahmad Syakir - the scholar cited by al-Qaradhawi as a supporter of calculations - al-Qaradhawi made some comments. These comments conclude that calculation must still consider the aspect of moon sighting and cannot stand alone. This shows the difference in views between Ahmad Syakir, a scholar who supports hishab absolutely, and al-Qaradhawi, who supports the use of hishab proportionally.